2019
DOI: 10.3389/fmars.2019.00711
|View full text |Cite
|
Sign up to set email alerts
|

Discriminating Natal Source Populations of a Temperate Marine Fish Using Larval Otolith Chemistry

Abstract: The life cycles of many marine species depend on a dispersive larval stage that connects spatially segregated populations. However, quantifying larval movement among populations remains one of the greatest challenges in marine ecology. Such movement determines whether a population is essentially a self-recruiting stock, or if it forms part of a larger meta-population where recruits originate from multiple sources. Previous research has struggled to differentiate between such stock structure models for King Geo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 69 publications
2
18
0
Order By: Relevance
“…In addition, physiological changes could occur in the transition to free-embryo or juvenile life (Lima et al ., 2012), which could cause changes in the rates of incorporation of Mn/Ca, Ba/Ca and Li/Ca. Similar to the present study, Mn/Ca (Rogers et al ., 2019) and Ba/Ca (Tabouret et al ., 2011) peaks were associated with the early stages (primordium) of several species such as Sicydium punctatum Perugia, 1896 and Sillaginodes punctatus (Cuvier, 1829). In C. spixii , the peaks were found on the margin of the primordium; there could be a potential physiological effect caused by metabolic changes (perhaps associated with ontogenetic changes) or a strong maternal/yolk influence which could mask the effect of other variables, such as environmental or physiological.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, physiological changes could occur in the transition to free-embryo or juvenile life (Lima et al ., 2012), which could cause changes in the rates of incorporation of Mn/Ca, Ba/Ca and Li/Ca. Similar to the present study, Mn/Ca (Rogers et al ., 2019) and Ba/Ca (Tabouret et al ., 2011) peaks were associated with the early stages (primordium) of several species such as Sicydium punctatum Perugia, 1896 and Sillaginodes punctatus (Cuvier, 1829). In C. spixii , the peaks were found on the margin of the primordium; there could be a potential physiological effect caused by metabolic changes (perhaps associated with ontogenetic changes) or a strong maternal/yolk influence which could mask the effect of other variables, such as environmental or physiological.…”
Section: Discussionmentioning
confidence: 99%
“…The incorporation of trace elements into otoliths can be influenced by environment (depth, salinity and temperature) (Lin et al, 2007;Reis-Santos et al, 2013); surrounding water chemistry (Avigliano et al, 2019;Elsdon, & Gillanders, 2003;Walther, & Thorrold, 2006); food (Ranaldi & Gagnon, 2008); genetics (Clarke et al, 2011); and physiological events such as hatching, transition to free embryo or juvenile life (Rogers et al, 2019;Tabouret et al, 2011);…”
Section: Discussionmentioning
confidence: 99%
“…The incorporation of trace elements into otoliths can be influenced by environment (depth, salinity and temperature) (Lin et al ., 2007; Reis‐Santos et al ., 2013); surrounding water chemistry (Avigliano et al ., 2019; Elsdon, & Gillanders, 2003; Walther, & Thorrold, 2006); food (Ranaldi & Gagnon, 2008); genetics (Clarke et al ., 2011); and physiological events such as hatching, transition to free embryo or juvenile life (Rogers et al ., 2019; Tabouret et al ., 2011); and even a differential fishing pressure among catchment areas could alter the otolith composition (Catalán et al ., 2018). Also, in species with prolonged yolk feeding, the recent life history of mothers (maternal effect) could have an influence on the incorporation of trace elements into the larval otolith (Kalish, 1990; Liberoff et al ., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with previous studies, the model predicted that larvae settle to nursery areas short distances from regional spawning grounds. In both gulfs, simulated connectivity between spawning grounds and nursery areas was supported by similarities in otolith chemistry between larvae and recruits (Fowler, Black, et al, 2000;Rogers et al, 2019aRogers et al, , 2019c.…”
Section: Implications For Stock Structurementioning
confidence: 91%
“…The third study identified two spatially segregated groups of larvae within the large spawning area that had different otolith chemistries. This indicated that southern Spencer Gulf and Investigator Strait supported two independent spawning populations (Rogers, Fowler, Steer, & Gillanders, 2019a). The aim of this study was to investigate the connectivity between spawning grounds and nursery areas by simulating dispersal using a biophysical model.…”
Section: Introductionmentioning
confidence: 99%